Plastics and its effect to women reproductive systems - Lestari, Pudji (Universitas Airlangga, 2020)
Since it was found in 1940's, the use of plastic has become a habit, as it is convenient and cheap. It products in a world scale more than 300 million tonnes. What we have to pay for that convenience and cheapness is now obvious. The waste of plastic goods is everywhere. Nowadays, even in rural areas, plastic waste pollutes the environment. Even in the middle of the oceans, islands of plastic refuse are there in the currents.These garbages are deadly to marine life. Globally, we now discard about eight million tonnes of plastics. When it ends up in the seas, fish and turtles take it as a food, swallow it to death or die of starvation because what they have consumed is not real food.